OXIDATIVE STRESS IN CHRONIC RENAL FAILURE - G.ARUNA; K.AMBIKA DEVI (International Journal of Pharma and Bio Sciences, 2014)
Chronic renal failure applies to the process of continuing significant irreversible reduction in the nephron number and corresponds to Chronic Kidney Disease (CKD) with the classification of 3-5. Lipid peroxidation is a continuous chain reaction providing a continuous supply of free radicals. Vitamin E an antioxidant forms the 1st line of defense against peroxidation of membranes of the cell and subcellular organelles.To compare Malondialdehyde,Vitamin E and other biochemical parameters in chronic renal failure with those of healthy controls.Sixty cases of both sexes with chronic renal failure from 35-60 years age group were selected. Control group includes 20 healthy individuals. Urea, Creatinine, Malondialdehyde, Vitamin E were compared in chronic renal failure with those of healthy controls. Creatinine Clearance was estimated by using Cock Croft and Gault formula to assess the renal function. The results were statistically analyzed by t- test and Pearson correlation.MDA levels were found statistically highly significant in CRF patients as compared to controls. Vitamin E levels showed significant decrease in CRF patients as compared to control group.The groups mean predicted Creatinine Clearance from the Cock Croft and Gault formula was 7.24 ml/min. Serum MDA and Serum Creatinine were positively correlated with severity and duration of CRF. Vitamin E was decreased in all the cases of CRF.